APPLICATION OF ISLAMIC BUSINESS ETHICS IN RICE BUYING AND BUYING TRANSACTIONS IN TRADITIONAL MARKETS - Zaitun Fitri (Al-Qardhu, 2023)
This article examines the application of Islamic business ethics in traditional markets. The main problem studied is the extent to which traders apply Islamic business ethics in carrying out trade transactions in traditional markets. In this research, researchers used qualitative research methods, namely a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior. The reason researchers use a qualitative approach is so that they can get as much information as possible, namely in the form of concepts, information, impressions and responses to the problems that researchers are studying so that it will be clear. After conducting long research, the author found that the application of Islamic business ethics cannot be applied by rice traders as business people in the Tanjung market. This can be seen from the answers of buyers and based on the results of observations obtained by researchers, there are still many traders who sell quality rice. poor with good quality rice, and traders also have not provided information if there are defects in the goods sold and have not been able to provide satisfaction with the service and quality of the rice sold to consumers, the lack of friendliness of traders towards buyers.